2008
DOI: 10.1007/s00428-008-0577-x
|View full text |Cite
|
Sign up to set email alerts
|

A score based on microscopic criteria proposed for analysis of papillary carcinoma of the thyroid

Abstract: Morphologic examination is the gold standard for diagnosing papillary thyroid carcinoma (PTC). This diagnosis, especially for the follicular variant, may be variable even among experts. Our objective was to analyze the frequency of PTC microscopic criteria in a series of thyroid tumors including follicular adenoma (FA) and PTC to build a score which could constitute a novel way for microscopic analysis of such thyroid tumors. Sixty-six PTC and 66 FA were matched for age, sex, and thyroiditis. Two independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…For these authors, the presence of nuclear pseudo inclusions was the less frequent finding among all tumours (54%). Similar results were also seen in a study conducted by Verhulst et al who stressed the importance of ovoid nucleus, enlarged nuclei, dark staining colloid, lack of polarisation, nuclear grooves in determining malignant status of the lesions [9].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For these authors, the presence of nuclear pseudo inclusions was the less frequent finding among all tumours (54%). Similar results were also seen in a study conducted by Verhulst et al who stressed the importance of ovoid nucleus, enlarged nuclei, dark staining colloid, lack of polarisation, nuclear grooves in determining malignant status of the lesions [9].…”
Section: Discussionsupporting
confidence: 87%
“…Clearing is said when nucleus shows peripheral condensation of chromatin giving it vesicular appearance and nuclear grooving when nucleus folds into itself [9]. About 70% of PTC cases in our study showed clearing followed by 41% of cases showing grooving.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…According to Livolsi et al strict criteria for specific nuclear features comprising of ovoid nuclei, crowded nuclei, clear nuclei, intranuclear grooves and inclusions should be applied to diagnose FVPC [7]. They also observed that other favorable features included psammoma bodies and secondary features such as elongated irregularly shaped follicles, dark staining colloid, and multinucleated histiocytes in the lumen of the follicles [5].…”
Section: Discussionmentioning
confidence: 99%
“…Chan proposed criteria for the diagnosis of encapsulated FVPC which include clear nuclei, round to oval nuclei, crowded nuclei, intranuclear grooves, psammoma bodies and secondary features like irregular follicles, thick colloid and multinucleated histiocytes [1]. A scoring system was applied for the diagnosis of PTC by Verhulst et al who observed that follicular patterned PTC was at or below the threshold score [7].…”
Section: Introductionmentioning
confidence: 99%